Danger theory inspired intrusion detection model for wireless sensor networks - Rong-rong FU; Kang-feng ZHENG; Tian-liang LU; Yi-xian YANG (Tongxin xuebao)
According to the challenges of intrusion detection technique for wireless sensor networks,a danger theory in-spired intrusion detection model was proposed by taking advantage of the working principle of artificial immune system.Due to the distributed and cooperative mechanism,the proposed model shows more advantages in detection performance and energy consumption than methods adopt promiscuous to get global knowledge.The simulation results show that compared to traditional Watchdog algorithm with single threshold and self-nonself(SNS)model,the model inspired by danger theory can provide highest correct detection rate and lowest false detection rate.Moreover,the model can also decrease the energy consumption of the system.